Keratinoctye-neuro-immune-units (KNICUs): collaborative impact on the initiation and maintenance of psoriasis - Chen, Xue-Yan; Wang, Zhao-Yuan; Zhou, Yuan; Ye, Li-Ran; Man, Xiao-Yong (Frontiers in Medicine, 2023)
The skin is the outermost barrier that separates the human body from the external environment. In psoriasis, immune cells reside within or infiltrate the epidermis to form the epidermal (epithelial) immunological microenvironment (EIME) and engage in complex interactions with keratinocytes, nerves, and microbiota. The proposed hypothesis is that psoriasis is a chronic inflammatory disease mainly mediated by a specific inflammatory environment composed of keratinocyte–neuro–immune cell units (KNICUs). These KNICUs arise from the interaction between activated epidermal keratinocytes, nerves, immune cells, and the skin microbiota, forming a complex interaction framework. Multiple units gather to complete the circulatory and amplified loops, consequently serving as a group army to initiate and maintain psoriasis.